Drivers of compositional turnover of narrow-ranged versus widespread naturalised woody plants in South Africa - de Beer, Isabella W.; Hui, Cang; Botella, Christophe; Richardson, David M. (Frontiers in Ecology and Evolution, 2023)
Introduction Alien trees and shrubs have become increasingly common invaders globally and have caused major negative impacts to ecosystems and society. Non-native woody plant species make up the majority of legislated invasive alien taxa in South Africa and contribute substantially to recorded negative impacts. It is of management interest to elucidate the macroecological processes that mediate the assembly of alien taxa, as this is expected to be associated with anthropogenic factors (e.g., human activity, introduction events, pathways of propagule dispersal mediated by humans) and bioclimatic factors (such as diurnal temperature range and precipitation gradients). These analyses require large species-occurrence datasets with comprehensive sampling across broad environmental conditions. Efforts of citizen scientists produce large numbers of occurrence records in a consistent manner which may be utilised for scientific investigations. Methods Research Grade occurrence data on naturalised plants of South Africa were extracted from the citizen scientist platform iNaturalist. Sampling bias was mitigated using statistical modelling of background points estimated from a Target Group of species which identifies well sampled communities. The drivers of assembly for alien plants at different range sizes were identified using multi-site generalised dissimilarity modelling (MS-GDM) of zeta diversity. The predicted compositional similarity between all cells was computed based on the subset of identified well sampled communities and using generalised dissimilarity modelling (GDM). From this, alien bioregions were identified using a k-means cluster analysis. Results and Discussion Bioclimatic factors significantly influenced community turnover in inland areas with large diurnal temperature ranges, and in areas with high precipitation. Communities separated by large geographical distances had significantly different compositions, indicating little contribution of long-range propagule movement by humans, and the presence of localised introduction hubs within the country which harbour unique species compositions. Analyses also showed a significant contribution of road density to turnover, which may be moderated by the habitat service provided by road verges. The same is true for natural dispersal via rivers in arid areas. The distribution of naturalised tree and shrub species is geographically clustered and forms six alien bioregions that are distinct from the South African biomes defined by native species distributionanalysis.